Role of neuronavigation in the surgical management of brainstem gliomas - Zhang, Mingxin; Xiao, Xiong; Gu, Guocan; Zhang, Peng; Wu, Wenhao; Wang, Yu; Pan, Changcun; Wang, Liang; Li, Huan; Wu, Zhen; Zhang, Junting; Zhang, Liwei (Frontiers in Oncology, 2023)
Objective: NeuroNavigation (NN) is a widely used intraoperative imaging guidance technique in neurosurgical operations; however, its value in brainstem glioma (BSG) surgery is inadequately reported and lacks objective proof. This study aims to investigate the applicational value of NN in BSG surgery. Method: A retrospective analysis was performed on 155 patients with brainstem gliomas who received craniotomy from May 2019 to January 2022 at Beijing Tiantan Hospital. Eighty-four (54.2%) patients received surgery with NN. Preoperative and postoperative cranial nerve dysfunctions, muscle strength, and Karnofsky (KPS) were evaluated. Patients’ radiological features, tumor volume, and extent of resection (EOR) were obtained from conventional MRI data. Patients’ follow-up data were also collected. Comparative analyses on these variables were made between the NN group and the non-NN group. Result: The usage of NN is independently related to a higher EOR in diffuse intrinsic pontine glioma (DIPG) (p=0.005) and non-DIPG group (p<0.001). It was observed that fewer patients in the NN group suffered from deterioration of KPS (p=0.032) and cranial nerve function (p=0.017) in non-DIPG group, and deterioration of muscle strength (p=0.040) and cranial nerve function (p=0.038) in DIPG group. Moreover, the usage of NN is an independent protective factor for the deterioration of KPS (p=0.04) and cranial nerve function (p=0.026) in non-DIPG patients and the deterioration of muscle strength (p=0.009) in DIPG patients. Furthermore, higher EOR subgroups were found to be independently related to better prognoses in DIPG patients (p=0.008) Conclusion: NN has significant value in BSG surgery. With the assistance of NN, BSG surgery achieved higher EOR without deteriorating patients’ functions. In addition, DIPG patients may benefit from the appropriate increase of EOR.